Effect of one-time dextran-polyacrylamide polymer matrixes treatment on female reproductive function - Sribna, Valentyna A.; Kaleinikova, Oksana N.; Kuziv, Yulia I.; Vinogradova Anyk, Alena A.; Karvatskiy, Igor N.; Voznesenskaya, Tetiana Y.; Blashkiv, Taras V.; Kutsevol, Natalia V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: recently, it has been proved that copolymers with dextran cores and grafted polyacrylamide are effective in photodynamic and chemotherapy. However, further research is needed to define correct dosage and to assess the risks. Thus, animal studies are becoming more relevant to determine the effect of the treatment of such drug nano-systems on female reproductive function in particular. Methods: a technique for estimation of pre- and post-implantation death rates, in vitro meotic maturation of oocytes, double fluorescent vital assay and statistical analysis were used. The effects of a one-time treatment of different doses of dextran-polyacrylamide matrices and silver (Ag)-nanoparticles-dextran-polyacrylamide (AgNPs-D-PAA) on reproductive function, namely on 1) the number of oocytes isolated from one ovary and the meiotic maturation of such oocytes in vitro; 2) the indicators of cell viability of the cells of follicular environment of oocytes (FEO) and the cells of inguinal lymph nodes (ILN); 3) the pre- and post-implantation mortality rates and the number of live newborns (pups) were investigated in female mice. Results: no significant changes in the number of oocytes isolated from one ovary and meiotic maturation of such ovarian oocytes in vitro, the number of living cells of follicular environment of oocytes and the number of such cells with morphological signs of apoptosis and necrosis, pre- and post-implantation mortality rates of embryos and the number of live newborns (pups) have been established under conditions of one-time treatment with dextran-polyacrylamide at doses of 0.39 mg/kg and 3.90 mg/kg and Ag-nanoparticles-dextran-polyacrylamide at doses of 0.20 mg/kg and 2.00 mg/kg. Conclusions: branched polymer systems (dextran-polyacrylamide (D-PAA) polymer matrices) are promising materials for use in next-generation medicine.